Phenotype, genotype and glycaemic variability in people with activating mutations in the ABCC8 gene: response to appropriate therapy. Issue 5 (21st October 2019) - Reilly, F.; Sanchez‐Lechuga, B.; Clinton, S.; Crowe, G.; Burke, M.; Ng, N.; Colclough, K.; Byrne, M. M.
Abstract: Aims: To examine the phenotypic features of people identified with ABCC8‐maturity‐onset diabetes of the young (MODY) who were included in the adult 'Mater MODY' cohort and to establish their response to sulfonylurea therapy. Methods: Ten participants with activating ABCC8 mutations were phenotyped in detail. A 2‐hour oral glucose tolerance test was performed to establish glycaemic tolerance, with glucose, insulin and C‐peptide measurements taken at baseline and 30‐min intervals. Insulin was discontinued and sulfonylurea therapy initiated after genetic diagnosis of ABCC8‐MODY. A blinded continuous glucose monitoring sensor was used to establish glycaemic control on insulin vs a sulfonylurea. Results: The mean age at diagnosis of diabetes was 33.8 ± 11.1 years, with fasting glucose of 18.9 ± 11.5 mmol/l and a mean (range) HbA1c of 86 (51, 126) mmol/mol [10.0 (6.8, 13.7)%]. Following a genetic diagnosis of ABCC8‐MODY three out of four participants discontinued insulin (mean duration 10.6 ± 1.69 years) and started sulfonylurea treatment. The mean (range) HbA1c prior to genetic diagnosis was 52 (43, 74) mmol/mol (6.9%) and the post‐treatment change was 44 (30, 57) mmol/mol (6.2%; P =0.16). Retinopathy was the most common microvascular complication in this cohort, occurring in five out of 10 participants. Conclusions: Low‐dose sulfonylurea therapy resulted in stable glycaemic control and the elimination of hypoglycaemic episodes attributable to insulin therapy. The use of appropriate therapy at the early stages of diabetes may decrease the incidence of complications and reduce the risks of hypoglycaemia associated with insulin therapy. What's new?: Activating mutations in ABCC8 are a rare cause of diabetes mellitus that manifests first in adolescence and early adulthood, with phenotype variability among family members. We report on the successful switch to sulfonylureas after chronic insulin use in participants with activating mutations in ABCC8 . The individuals in our study cohort presented with dramatic hyperglycaemia with classic symptoms of diabetes. Diabetic retinopathy was the most common complication in the cohort. Early genetic confirmation of ABCC8‐maturity‐onset diabetes of the young (MODY) and appropriate sulfonylurea therapy would reduce episodes of hypoglycaemia and is likely to reduce diabetes complications. The study emphasizes the importance of the genetic characterization of ABCC8‐MODY to guide personalized treatment.